2021
DOI: 10.5089/9781513573717.001
|View full text |Cite
|
Sign up to set email alerts
|

Who Doesn’t Want to be Vaccinated? Determinants of Vaccine Hesitancy During COVID-19

Abstract: Quick vaccine rollouts are crucial for a strong economic recovery, but vaccine hesitancy could prolong the pandemic and the need for social distancing and lockdowns. We use individual-level data from nationally representative surveys developed by YouGov and Imperial College London to empirically examine the determinants of vaccine hesitancy across 17 countries and over time. Vaccine demand depends on demographic features such as age and gender, but also on perceptions about the severity of COVID-19 and side ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…For one thing, vaccine uptake was not made mandatory by the UK authority, but the decision on whether to get the jab was left to the individual. Arguably, such a decision is likely to be influenced by predetermined individual characteristics and tastes (Argote et al 2021;Dabla-Norris et al 2021;Borga et al 2022). For another thing, vaccine compliance is strongly influenced by the environment, that is, where and when this individual decision is taken.…”
Section: Empirical Strategymentioning
confidence: 99%
“…For one thing, vaccine uptake was not made mandatory by the UK authority, but the decision on whether to get the jab was left to the individual. Arguably, such a decision is likely to be influenced by predetermined individual characteristics and tastes (Argote et al 2021;Dabla-Norris et al 2021;Borga et al 2022). For another thing, vaccine compliance is strongly influenced by the environment, that is, where and when this individual decision is taken.…”
Section: Empirical Strategymentioning
confidence: 99%
“…The existing studies indicate the various range of factors that contribute to the COVID-19 mortality which includes gender (23,24), hesitancy of being vaccinated (15,25), age (6,10,21,22,(26)(27)(28)(29)(30)(31)(32)(33), environmental, demographic factors, population density, biological and healthcare related factors (2,3,16), race (12,(18)(19)(20)34), international travel (17), and pre-existing morbidity (7)(8)(9)(35)(36)(37)(38).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using this accumulated data, the study also revealed through it's SIR model, that the present, and future rates of vaccine hesitancy can severely impact the future trajectory of COVID-19 case counts, and subsequently, restrictions to mitigate the spread. This model forecasted, with the current rates of vaccine refusal, and hesitancy, that the count of cases, as well as deaths, and hospitalizations, will rise in the coming fall/winter months (Khan, 2021).…”
Section: Vaccine Development and Availabilitymentioning
confidence: 99%